The Scrutinizing Gaze in the Aesthetics of Islamic Visual Cultures: Sight, Insight, and Desire - Necipoğlu, Gülru (Muqarnas, 2015)
The subjectivity of the gaze and its engagement with human experience had the capacity to incorporate the body, affect, sensation, and memory, thereby raising the status of the visual arts and architecture into potential sites of knowledge. This essay engages with the subject of the gaze and aesthetic experience by exploring the wonderment of the eye, the embodiment of vision through emotional states and desire, the disembodiment of the eye in introspective vision, and the cognitive capacity of sight to produce insight. Addressing these diverse yet interrelated themes, it considers the modalities of the gaze in new genres of Safavid and Ottoman texts on the arts and architecture, starting with their origin in medieval paradigms of visual perception and artistic creation. These more specialized sixteenth–seventeenth-century Persian and Turkish sources include treatises on the visual arts, album prefaces, biographies of architects, and biographical anthologies of calligraphers and painter-decorators.